Applications and Science in Soft Computing - Lotfi, Ahamad; Garibaldi, Jonathan M. (Advances in Soft Computing, 2004)
The book covers the theory and application of soft computing techniques namely; neural networks, fuzzy logic, evolutionary computing and complex systems. The book is a collection of selected, edited papers presented at the 4th conference RACS Recent Advances in Soft Computing held in Nottingham, December 2002. It provides the latest developments in applications of soft computing techniques as well as advances in theoretical aspects of soft computing